Puberty in girls with Prader-Willi syndrome: cohort evaluation and clinical recommendations in a Latin American tertiary center - Passone, Caroline Gouveia Buff; Aragão, Luciana Felipe Ferrer; Franco, Ruth Rocha; Leite, Junia Ellen Simioni; Gonzalez, Michelle Antonella Benitez; Schil, Priscila Schuindt de Albuquerque; Ybarra, Marina; Damiani, Durval; Kerkhof, Gerthe Femke; Montenegro Junior, Renan Magalhães; Silva, Clovis Artur (Frontiers in Endocrinology, 2024)
Introduction: Prader-Willi syndrome (PWS) is a genetic disorder characterized by hypothalamic-pituitary deficiencies including hypogonadism. In girls with PWS, hypogonadism can present early in childhood, leading to genital hypoplasia, delayed puberty, incomplete pubertal development, and infertility. In contrast, girls can present with premature activation of the adrenal axis leading to early pubarche and advanced bone age. We aim to evaluate the progression of puberty and adrenarche signals in girls with PWS. Methodology: A longitudinal retrospective cohort study included girls with PWS followed at a Pediatric Endocrinology Outpatient Clinic in a Tertiary University Hospital in Sao Paulo, Brazil from 2002 to 2022. Data collected via chart review included clinical information on birth history, breast and pubic hair Tanner stages, presence of genital hypoplasia, age at menarche, regularity of menstrual cycles, body mass index (BMI) z-score, final height, age of initiation of estrogen replacement and growth hormone replacement, as well as results for PWS genetic subtype; biochemical investigation (LH, FSH, estradiol, DHEA-S); radiographic bone age and pelvic ultrasound. Results: A total of 69 girls were included in the study and the mean age of puberty onset was 10.2 years in those who started puberty after the age of 8 years. Breast Tanner stage IV was reached by 29.1% girls at a mean age of 14.9 years. Spontaneous menarche was present in 13.8% and only one patient had regular menstrual cycles. Early adrenarche was seen in 40.4% of cases. Conclusion: Our study demonstrated in a large sample that girls with PWS often present with delayed onset of puberty despite frequent premature adrenarche. Based on our results, we suggest an estrogen replacement protocol for girls with PWS to be started at the chronological age or bone age of 12-13 years, taking into consideration the uterus size. Further prospective studies are needed.